Meaning Of Speech Functions in the Fifth 2024 Indonesian Presidential Debate: A Discourse Analysis - Soegiarto, Herryono; Supatmiwati, Diah; Sudewi, Ni Ketut Putri Nila; Muhid, Abdul; Syamsurrijal, Syamsurrijal (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study is about the meaning of speech function in the 2024 Indonesian presidential candidate debates. The purpose of this study is to find out the meaning of speech function of the speech function in Indonesian 2024 presidential candidate debates based on Halliday (2024) classification of speech function. Qualitative research design is used to analyze the data. The result showed that all candidates predominantly utilized statements to convey their vision and mission, indicating a focus on asserting their positions and values. There were offer function employed by all the presidential candidates. The distribution of speech function offer could differ across the sources or speakers analyzed. Question function submitted by the first candidate which is two utterances. The question function delivered by the first candidate Anies Baswedan and the third candidate Ganjar Pranowo. The command utterance was only found in the third candidate Ganjar Pranowo speech.